The Impact of E-Training Model on the Improvement of Professional Competence of PAUD-DIKMAS Educators - Sutarto, Joko; Edi Mulyo, Sungkowo; Shofwan, Imam; Siswanto , Yudi (KnE Social Sciences, 2019)
Theface-to-facetrainingthathasbeencarriedoutallthistimeisconsideredincapable to fully improve the professional competence of trainees. So, it is needed an E-training model which is based on the needs of the trainees. The purpose of this study were: (a) to ﬁnd out and analyze the E-Training model implemented in the training of PAUDDikmas Educators and, (b) to analyze the impact of the implementation of E-Training models on the improvement of professional competence of PAUD-Dikmas Educators. The subjects of this research were the management and trainers, 8 people in total, to reveal data related to model design and 120 trainees (PAUD-Dikmas Educators) to reveal data about the impact of E-Training model implementation. The data collection methodsusedwereinterviewandquestionnaire.Thetechniquesusedtoanalyzewere descriptive-quantitative statistical analysis. The results of the study showed: (a) the implementation of E-Training model follows the ﬂow of activities: training problems and needs analysis, training socialization and trainees recruitment, training planning, training learning process including independent learning, assignment, unit evaluation, and mentoring, comprehensive evaluation through independent assignments, they are given a certiﬁcate if they passed, and follow-up in the form of competency tests, and advanced training; and (b) the implementation of the E-Training model had animpactontheimprovementofprofessionalcompetenceofPAUD-Dikmaseducators. Keywords: e-training model, professional competence